DISCONNECT youth's misuse of social media - Lazo, Lalaine S. (College of Fine Arts, University of the Philippines Diliman, 2016)
Researches have shown that excessive use of internet and social media is the cause of lack of interpersonal skills. The purpose of this thesis is to gain an in depth understanding of exactly what is the main cause of youth's declining interpersonal social skills and how can we possibly avoid it. According to Turkle's theory, social media gives a deception that we are connected. We put our attention wherever we want on anyone we know, that we can always be "heard" and the illusion that we never have to be alone. In order to gain the in depth knowledge required for the thesis a case study methodology will be utilized with interview on psychologists, parents, on-site/ online survey on youth. Analyzing the data, the results reveal that despite the longer time using the social media it's not cause of the problem but it's actually the misuse. Young people should understand the importance of social relation. Parent must take the initiative to educate and guide their children the proper use of social media. Formulated a possible solution by showing the real situation of teenagers and youth nowadays, how they response and act on social media portals like facebook, Instragram, twitter. A short film which can show the misuse and how parents or individual could solve these problems.